Genetic Analysis and Distribution of F2 Population Variety of Tomato Crosses - Muh. Farid BDR; M. Alfan Ikhsanul Amal; Siti Antara Maedhani Tahara; Nuriyah Magfiratul Fara Ramadhani; Ihsan Syawal Rahmat (Universitas Sembilanbelas November Kolaka, 2021)
The demand for tomatoes is increasing along with population growth. However, this demand needs to be supported by increasing tomato productivity. One way to increase this is the assembly of high-yielding tomato varieties. In the assembly of varieties, the F2 generation is a generation with high diversity. This becomes important in the process of evaluating and selecting tomato varieties. Genetic variants are the initial capital of plant breeding efforts, which are related to the assembly of varieties to increase the quantitatively and quality of the yield including fruit size, fruit quality and productivity by utilizing the heterotic phenomenon in the assembly of tomato varieties. A research was conducted to evaluate the diversity of generations of biparental crosses using an augmented design. The genotypes used were Mawar (30 plants), Karina (30 plants), F1 genotype of Mawar x Karina (25 plants), Mawar x Karina x Mawar (20 plants), Mawar x Karina x Karina (20 plants), and F2 genotype of Mawar x Karina (200 plants) which were divided into 4 blocks. The results show that the genetic diversity of the F2 population was highest in the characters of plant height, harvest age, fruit length and fruit diameter, with heritability values in the medium to high category